Evaluation model of career counseling program in vocational high school - Sri Tutur Martaningsih; Soenarto Soenarto; Edi Istiyono (International Journal of Evaluation and Research in Education (IJERE), 2019)
ocational high school graduates are expected to readily enter the work field, nevertheless, the number of unemployment from vocational high school graduates is still big. Optimizing a career guidance service requires complete evaluation feedback. In detail, this research aims to: identifying a construct instrument applicable to evaluate a career guidance program at vocational high school; Developing an evaluation model; and Examining the measurement, structure and the effectivity of the model. The research’s approach and development employ Borg & Gall’s Model. The test toward the product is addressed to nine vocational high schools in Yogyakarta. The validity and reliability instruments are verified through expert judgment, alpha Cronbach analysis, Exploratory Factor Analysis (EFA), testing the measurement model, and for the structural model, it is verified by means of partial least square (PLS) SmartPLS 3.0. The product constitutes a career guidance evaluation model at vocational high school, complete with its application, manipulation, and analysis up to recommendation construction. The result of the EFA test shows six measurement factors of counseling service: assertiveness, career readiness, self-awareness, career awareness, work characteristics, and positive attitude towards guidance and counseling service. The quality instrument product of TADIPHE consists of the target component (3 items), assessment (13 items), design (13 items), installation (22 items) process (44 items), the result (70 items), and effectiveness of the program (7 items). The result of the partial least square shows that all predictors contribute (Q2) as much as 88.91%, and 11.09 % and the rest may be determined by other variables.